Introducing an ecologically-based pest management approach in Cambodia through adaptive learning networks - Flor, Rica Joy; Maat, Harro; Stuart, Alexander; Then, Rathmuny; Choun, Saban; Chhun, Sokunroth; Hadi, Buyung Asmara Ratna (SAGE Publications, 2023)
How can we reach farmers with ecologically-based Integrated Pest Management (IPM) while creating a supportive context for adoption by farmers and relevant stakeholders? We assessed a new method – Adaptive Learning Networks – from reflections of varied stakeholders, farmer diaries and survey data procured in 2016 and 2019. This method is different from current IPM approaches, in that an explicit focus of learning was on engaging other stakeholders to enable adoption by farmers. For example, access to IPM products, providing new services and creating new policies were intrinsically part of the learning process, alongside learning on-farm IPM techniques. The main consideration is to ease farmers from being locked into the practice of pesticide reliance. The method facilitated multi-stakeholder learning that led to an adaptation of the IPM tools and techniques in the case examined. The priority of this new method was socio-technical learning, wherein varied stakeholders modify interactions, incentives and arrangements relating to pest management. Comparing 2016 and 2019 data, there was a significant reduction in insecticide, herbicide, and rodenticide applications. The observed outcomes indicate the potential to enable a wider spread of IPM technologies